2010
DOI: 10.4049/jimmunol.0903238
|View full text |Cite
|
Sign up to set email alerts
|

T Cell Pathways Involving CTLA4 Contribute To a Model of Acute Lung Injury

Abstract: Acute lung injury (ALI) is a frequent pulmonary complication in critically ill patients. We characterized a murine model of LPS-induced ALI, focusing on Th cells. Following LPS administration, bronchoalveolar lavage lymphocytes, neutrophils, IL-6, TNF-α, and albumin were increased. Analysis of LPS-induced T cells revealed increased Th cell-associated cytokines (IL-17A, -17F, and -22), as well as increased expression of CD69 (a cell activation marker), Foxp3, and CTLA4 in CD4+ T cells. Administration of anti-CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 34 publications
(31 reference statements)
4
39
0
Order By: Relevance
“…[40][41][42] Furthermore, airway smooth muscles present from the bronchial tree up to the terminal bronchioles are highly activated during inflammation and lung tissue damage with engagement of TLRs promoting nonspecific airway hyperresponsiveness. Therefore, LPS instillation provides a useful experimental system for investigating the mechanisms of AHR in anesthetized and ventilated mice.…”
mentioning
confidence: 99%
“…[40][41][42] Furthermore, airway smooth muscles present from the bronchial tree up to the terminal bronchioles are highly activated during inflammation and lung tissue damage with engagement of TLRs promoting nonspecific airway hyperresponsiveness. Therefore, LPS instillation provides a useful experimental system for investigating the mechanisms of AHR in anesthetized and ventilated mice.…”
mentioning
confidence: 99%
“…Lungs were harvested at 48 hours after LPS exposure. Bronchoalveolar lavage (BAL) fluid and BAL cells were collected as previously described (22). I-cAMP and anti-cAMP antibody.…”
Section: Acute Lung Injury Modelmentioning
confidence: 99%
“…We previously showed that CTLA4 expression is increased in an LPS-induced model of acute lung injury (ALI), then tested whether LPS modifies CTLA4 at the level of transcription (22). We analyzed LPS stimulation of the CTLA4 promoters at different time points.…”
Section: Rapamycin Decreases Lps-or Camp-induced Ctla4 Transcriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Th17 cells play potent pro-inflammatory roles by secreting cytokine IL-17A, IL-22, IL-6, and TNF-α [15,19]. IL-17 potently induces the production of IL-8 and G-CSF from epithelial cells and fibroblasts, thereby resulting in neutrophil activation and recruitment.…”
Section: Introductionmentioning
confidence: 99%